Serodiagnostic evaluation of fusion proteins from multiple antigens of Mycobacterium tuberculosis for active TB. (March 2021) - Arif, Shaista; Akhter, Mohsina; Khaliq, Aasia; Nisa, Zaib un; Khan, Imran H.; Akhtar, Muhammad Waheed
Abstract: Tuberculosis (TB) is a global health problem, being prevalent in the developing countries. A rapid, reliable and cost effective diagnostic method would help in controlling TB in the endemic populations. Development of suitable fusion molecules detecting multiple antibodies produced against Mycobacterium tuberculosis antigens would enhance sensitivity of serodiagnostic assays. In this study, EspC, CFP7 and PPE57 antigens of M. tuberculosis were selected for constructing fusion molecules after prediction of B-cell epitopes using in silico tools. Fusion proteins EspC-CFP7, HspX-EspC-CFP7 and HspX-EspC-CFP7-PPE57 were expressed in E.coli (BL21). The serodiagnostic potential of the individual antigens and their fusions was analyzed by screening 230 plasma samples of pulmonary TB patients. The single antigens HspX, EspC, CFP7, PPE57 showed sensitivities of 30%, 31%, 22% and 35%, respectively. The fusion protein EspC-CFP7 showed sensitivity of 43%. Linking of HspX antigen to the N-terminus of EspC-CFP7 fusion molecule increased sensitivity to 58%, while joining PPE57 antigen to the C-terminus of HspX-EspC-CFP7 increased sensitivity to 69%. The fusion protein HspX-EspC-CFP7-PPE57 seems to be a promising molecule for use in the development of fusions with higher sensitivity. Highlights: Single B-Cell epitope for EspC and CFP7 whereas 3 epitopes for PPE57 were predicted for first time through in-silico tools. Linking HspX to the N-terminus of EspC-CFP7 resulted in the soluble expression and higher sensitivity of the fusion protein. HspX-EspC-CFP7-PPE57 fusion construct with enhanced sensitivity may be a promising molecule for the serodiagnosis of TB.